Incidence and Outcome of Pericardial Effusion in Pediatric Patients After Hematopoietic Stem Cell Transplant: A Single-institution Experience. Issue 2 (March 2018) - Diamond, Melissa; Ruiz-Mesa, Catalina; Corrales-Medina, Fernando F.; Tamariz, Leonardo J.; Ziga, Edward; Swaminathan, Sethuraman
Abstract : Background: Pericardial effusion (PE) is a known complication after hematopoietic stem cell transplant (HSCT). Limited data is currently available regarding the incidence and outcomes of PE in pediatric HSCT. Methods: We conducted a retrospective study on a cohort of patients who underwent HSCT between 2004 and 2015. Risk factors associated with development of PE were evaluated. Results: In 111 HSCT, stem cell source was bone marrow in 37 (33.3%), peripheral blood—42 (37.8%) and cord blood—32 (28.8%). Incidence of PE after HSCT was 37.8%. Insignificant effusion (trivial or small) was noted in 30 (27.0%) transplants, and significant (moderate or large) PE in 12 (10.8%). There were no associations between incidence of effusion and stem cell source, graft versus host disease or CMV infection. Risk factors associated with development of PE included systemic hypertension ( P <0.05), total body irradiation ( P <0.05), and sinusoidal obstruction syndrome formerly known as venoocclusive disease ( P =0.03). Overall mortality was 22.5% after HSCT, but 38.1% among those with effusion ( P <0.05). None of these deaths were attributed to primary cardiac etiologies. Conclusions: The incidence of PE in this cohort of pediatric HSCT recipients is high and associated with higher morbidity and mortality.